Towards a Holistic Assessment Framework: Integrating Islamic Values into Madrasah Curriculum Evaluation - Hasibuan, Arfin; Nurhalimah, Nurhalimah; Lubis, Zultoni; Barus, Yenita Anggraini (JURNAL AL-TANZIM, 2026)
The Islamic education value-based curriculum evaluation system is an important element in realising holistic madrasah education. This study aims to analyse the Islamic education value-based curriculum evaluation system in madrasahs, including planning, evaluation models, and implementation effectiveness. This study uses a qualitative case study approach that integrates in-depth interviews, observations, and document analysis. The uniqueness of this study lies in its holistic approach, which combines authentic, character-based, and habituative assessment models to measure students’ cognitive, affective, spiritual, and social aspects. The results of the study show that the evaluation plan was systematically developed in accordance with KMA Number 1503 of 2025 and integrated Islamic values into learning indicators, attitude assessment, worship, and morals. Evaluation has evolved into a holistic assessment that covers cognitive, affective, spiritual, and social aspects through authentic assessment, observation, attitude journals, and religious habits. The evaluation model applied is effective in shaping students’ discipline, honesty, responsibility, and awareness of worship. This research reinforces the importance of Islamic value-based evaluation, strengthens Islamic character and the quality of madrasah education, and makes new contributions to Islamic education research through a holistic, integrated evaluation approach.